2015
DOI: 10.1002/2014jc010390
|View full text |Cite
|
Sign up to set email alerts
|

Decadal variations in trace metal concentrations on a coral reef: Evidence from a 159 year record of Mn, Cu, and V in a Porites coral from the northern South China Sea

Abstract: Geochemical cycles of trace metals are important influences on the composition and function of the marine ecosystem. Although spatial distributions of most trace metals have now been determined in at least some parts of the oceans, temporal variations have barely been studied on account of data limitations. In this paper, we report on a 159 year record of trace metal concentrations from a Porites coral from the northern South China Sea (SCS), and discuss how oceanic and climatic processes control variations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 81 publications
(137 reference statements)
3
20
0
Order By: Relevance
“…[] again indicate that the seawater nutrients on the coral reefs in this region are significantly enriched when the Qiongdong upwelling is activated. Thus, the Qiongdong upwelling may be very important for supplying nutrients to this region [ Chen et al ., a].…”
Section: Discussionmentioning
confidence: 99%
“…[] again indicate that the seawater nutrients on the coral reefs in this region are significantly enriched when the Qiongdong upwelling is activated. Thus, the Qiongdong upwelling may be very important for supplying nutrients to this region [ Chen et al ., a].…”
Section: Discussionmentioning
confidence: 99%
“…The sampling locations are shown in Figure 1. The modern coral 11LW4 was used previously to study decadal variability in the northern SCS [Deng et al, 2013;Chen et al, 2015;Wei et al, 2015].…”
Section: Methodsmentioning
confidence: 99%
“…Then, X-ray photographs were taken to reveal the regular and well-defined annual density bands, which were used to establish the coral chronology. The X-radiographs of the coral 11LW4 refer to Chen et al [2015], and those of other corals are presented in supporting information Figure S1. Next, the coral slices were soaked in 10% H 2 O 2 for 24 h to remove organic matter, and this was followed by ultrasonic cleaning in deionized water for 30 min to remove surface contaminates.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, Kim (2011, 2014) showed that SGD was a major source of REE in local coastal waters. Given the lack of covariance between the REE/Ca and Mn/Ca ratios (Chen et al, 2015;Fallon et al, 2002;Lewis et al, 2007) (Table 1), as well as the absence of large surface runoff from rivers and volcanic eruptions near the study area, SGD may be the primary controlling factor for REE variability in the coral records.…”
Section: Control Of Ree and Ba In Coastal Seawatersmentioning
confidence: 99%